JENIS DAN POPULASI LALAT PADA TERNAK SAPI DI DESA TOLOK, KECAMATAN TOMPASO, KABUPATEN MINAHASA - Djenaan, Faris; Assa, G.V.J.; Poli, Z.; Lomboan, A. (Universitas Sam Ratulangi, 2019)
TYPES AND POPULATION OF FLY ON BEEF CATTLE AROUND TOLOK VILLAGE AT TOMPASO DISTRICT OF MINAHASA REGENCY. The Study was conducted to evaluate types and population of fly on beef cattle around Tolok village at Tompaso district of Minahasa regency. Observation was applied during a month involving sixteen beef cattle. Flies were cached using insect net one time on every two weeks. Collections of flies were conducted three times and types of fly were also identified including their population. Results of observation showed that there were three types fly on beef cattle including Haematobia exigua, Stomoxys Calcitrans and Musca domestica. The population of these flies were Haematobia exigua of 94.43 individuals, Stomoxys Calcitrans of 10.49 individuals and Musca domestica of 7.74 individuals. The dominant fly during collection at Tolok village was type of Haematobia exigua.Â Key words: Fly population, dominating fly type, beef cattle.